2013
DOI: 10.1038/nature12036
|View full text |Cite
|
Sign up to set email alerts
|

An electrically pumped polariton laser

Abstract: Conventional semiconductor laser emission relies on stimulated emission of photons, which sets stringent requirements on the minimum amount of energy necessary for its operation. In comparison, exciton-polaritons in strongly coupled quantum well microcavities can undergo stimulated scattering that promises more energy-efficient generation of coherent light by 'polariton lasers'. Polariton laser operation has been demonstrated in optically pumped semiconductor microcavities at temperatures up to room temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
339
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 480 publications
(355 citation statements)
references
References 28 publications
6
339
0
4
Order By: Relevance
“…2(a). Confirming the observations that we have reported previously [9], we observe a double threshold in the input-output characteristics [35][36][37][38], which strongly suggests a crossover from the linear regime to polariton lasing (at j = 50 A/cm 2 , and a subsequent transition (at j = 110 A/cm 2 ) into the regime of cavity mediated from an electron-hole plasma. It is worth noting that while the second threshold into the weak coupling regime acquires the shape of a smooth S in the double logarithmic plot, the polariton lasing threshold features a sudden increase in intensity.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…2(a). Confirming the observations that we have reported previously [9], we observe a double threshold in the input-output characteristics [35][36][37][38], which strongly suggests a crossover from the linear regime to polariton lasing (at j = 50 A/cm 2 , and a subsequent transition (at j = 110 A/cm 2 ) into the regime of cavity mediated from an electron-hole plasma. It is worth noting that while the second threshold into the weak coupling regime acquires the shape of a smooth S in the double logarithmic plot, the polariton lasing threshold features a sudden increase in intensity.…”
supporting
confidence: 91%
“…The intrinsic λ-thick GaAs Fabry-Pérot cavity spacer contains four InGaAs quantum wells (QWs). Strong coupling conditions are confirmed by photoreflection measurements and angular resolved electroluminescence for various excitonphoton detuning conditions, and we can extract a Rabi splitting of 5.5 meV (6 meV for a magnetic field of 5 T) [9]. In order to facilitate efficient current injection into the QWs, we etch micropillars with a diameter of 20 μm into the layer structure, which are later planarized by a polymer (benzocyclobuthene), and ring contacts are lithographically defined and evaporated on the top of the pillars.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…For a hybrid structure illustrated in Fig.1a, we encounter radiative field modes, such as photons and polaritons [13][14][15][16][17], as well as evanescent field modes, e.g., surface and graphene plasmons [18][19][20]. Research on optical responses of graphene electrons has been reported previously [20,21], but most of those efforts have been limited to the radiation or grating-deflection field coupling.…”
mentioning
confidence: 99%